2012
DOI: 10.1038/leu.2011.392
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic analyses identify WEE1 as a critical mediator of cell fate and a novel therapeutic target in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) remains a therapeutic challenge despite increasing knowledge about the molecular origins of the disease, as the mechanisms of AML cell escape from chemotherapy remain poorly defined. We hypothesized that AML cells are addicted to molecular pathways in the context of chemotherapy and used complementary approaches to identify these addictions. Using novel molecular and computational approaches, we performed genome-wide shRNA screens to identify proteins that mediate AML cell fate aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…17 These analyses revealed 206 genes involved in modulating the cellular response to prednisolone in ALL, including 102 identified by both analyses (P , 1 3 10 230 ; Figure 1B Figure 2). Notably, genes associated with kinase signaling were the most enriched category, many of which are associated with MAPK signaling cascades ( Figure 1D and supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 These analyses revealed 206 genes involved in modulating the cellular response to prednisolone in ALL, including 102 identified by both analyses (P , 1 3 10 230 ; Figure 1B Figure 2). Notably, genes associated with kinase signaling were the most enriched category, many of which are associated with MAPK signaling cascades ( Figure 1D and supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Viral preparation, genome-wide shRNA screening, 17 real-time quantitative polymerase chain reaction, 18 apoptosis assays, 18 cell viability assays, 18 immunoblots, 18 phospho flow cytometry, 19 and xenograft models [20][21][22][23] were all performed as previously described with additional details and modifications available in the supplemental Methods, found on the Blood Web site.…”
Section: Additional Methodsmentioning
confidence: 99%
“…36,40,51,52 The combined cytarabine and MK-1775 treatments resulted in synergistic inhibition of proliferation, regardless of p53 status. 40 It has been demonstrated that cytarabine-induced S-phase cell cycle arrest was overcome by the addition of MK-1775.…”
Section: Discussionmentioning
confidence: 99%
“…40 It has been demonstrated that cytarabine-induced S-phase cell cycle arrest was overcome by the addition of MK-1775. 40, 51,52 Tibes et al used an RNAi screening approach to identify kinases involved in cytarabine sensitivity and found ATR, PKMYT1, and CHK1, among others, as kinases involved in cytarabine sensitivity. 36 In addition, they demonstrated synergistic anti-leukemic activity for combined MK-1775 and cytarabine treatment in cell line models.…”
Section: Discussionmentioning
confidence: 99%
“…The signature mainly consisted of loci that were significantly demethylated during commitment from STHSC to CMP (516/561 loci, 92.0%). Interestingly, this stem cell commitment-associated epigenetic signature was enriched in loci associated with several genes that are commonly implicated not only in human HSC function and commitment but also in leukemogenesis, such as CEBPA (27)(28)(29), E2F1 (30), KRAS (31,32), and WEE1 (33) as well as a noncoding transcript, MIRLET7B (ref. 34 and Supplemental Table 4).…”
Section: Introductionmentioning
confidence: 99%